Cultural Communication in Promoting Tebing Tinggi Local Wisdom through Putera Puteri Tebing Tinggi’s Instagram - Fathir Syah Amir Sitompul; Nursapia Harahap (Jurnal IPTEK Bagi Masyarakat, 2026)
Social media enables local organizations to introduce cultural identity and local values to wider audiences. This study analyzes how the Instagram account of Putera Puteri Tebing Tinggi promotes the local wisdom of Tebing Tinggi City from a cultural communication perspective. A descriptive qualitative approach was used, with data collected through observation of Instagram posts, content documentation, and interviews with account managers. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña through data reduction, data display, and conclusion drawing. The findings show that the account is used mainly for organizational publication, event promotion, and participant image building rather than for sustained promotion of local wisdom. Local cultural elements, such as traditional attire, appear in several posts, but are rarely supported by educational narratives explaining their meanings, values, and contexts. The account therefore has strong potential as a cultural communication medium, but requires a more focused content strategy. Recommended actions include developing a cultural content calendar, creating regular local wisdom education rubrics, and collaborating with cultural communities to strengthen the promotion of local culture.